Intangible roles: Theory, policy, practice and intangible cultural heritage - Littler, Jo (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2014)
The emphasis on non-material knowledge and forms of communication in intangible cultural heritage can be related both to the expansion of curatorial interest in “experiential” displays and to the valorisation of what has, more broadly, been termed the “experience economy” in contemporary society. The recent interest in intangible cultural heritage, in other words, might usefully be situated in the context of what has been called “the cultural turn.” Given this context, the author of this article considers how the case of intangible cultural heritage throws two particular issues into stark relief: first, heated contemporary debates over the desirability of academics engaging with the administration of culture – over whether engaging with policy is an abdication of political possibility – and second, the boundaries of cultural policy, or what it is possible to administer. Positioning itself against a narrowly technocratic approach, the paper argues that we need to interrogate the cultural heritage of intangible cultural heritage itself. By doing so, we will be better equipped to consider what capacious, imaginative interactions between theory, policy, process and practice might look like.